Quantitative IVIM parameters evaluating perfusion changes in brain parenchyma in patients newly diagnosed with acute leukemia: Compared with healthy participants - Cui, Jianing; Zheng, Jing; Niu, Weiran; Bian, Wenjin; Wang, Jun; Niu, Jinliang (Frontiers in Neurology, 2023)
Purpose To study the value of quantitative IVIM parameters in evaluating cerebral blood perfusion changes in newly diagnosed AL patients by comparing with healthy participants. Results Forty healthy participants and forty-nine newly diagnosed AL patients were evaluated. The results showed that in 40 healthy participants, the sADC, D, f and PDR values of GM were significantly higher than that of WM (t =5.844, P= 0.000 and t = 3.838, P= 0.000, t = 7.711, P = 0.000 and Z=-2.184, P=0.029 respectively); in 49 AL patients, the sADC, D and f values of GM were significantly higher than that of WM (t=3.450, P=0.001, t=6.262, P=0.000 and t=4.053, P=0.000 respectively); in 40 healthy participants and 49 AL patients, in GM, the sADC and f values of AL were significantly lower than that of healthy participants (z=-2.537, P= 0.011, z=-2.583, P= 0.010, respectively); in WM, the sADC and f values of AL were significantly lower than that of healthy participants (z=-2.969, P= 0.003, z=-2.923, P= 0.003, respectively); the WBC count of 49 AL patients were significantly higher than that of 40 healthy participants(t=3.147, P=0.002). Multivariate analyses showed that f values of GM and WM were independent predictors of AL (P=0.03, and 0.01, respectively). In ROC analysis, the f value of GM (cutoff of 7.08%) had sensitivity of 98%, specificity of 11.4%, and AUC of 0.661; and sADC of WM (cutoff of 0.79×10-3mm2/s) demonstrated sensitivity of 94%, specificity of 56.4%, and AUC of 0.767. The f value of WM (cutoff of 13.77%) achieved sensitivity of 59.2%; specificity of 79.5%, and AUC of 0.682. Conclusion The IVIM parameters of brain parenchyma in newly diagnosed AL patients were different from healthy participants. The changes of cerebral blood flow perfusion are expected to provide new ideas for the study of central nervous system infiltration in AL.